Основные проблемы развития предпринимательства в НКР на современном этапе - Ишханян, Ирина; Ишханян, Григорий
The issues of economic stabilization and recovery, development of the industry and other sectors of NKR economy, improvement of the welfare and the living standard of the population are connected with the implementation of radical reforms in post-Soviet period. The development of the market economy in the NKR requires doing away with a number of problems, including the above-mentioned; and this can be achieved only when the necessary conditions for creating development of the entrepreneurship are provided. The article discusses the main problems connected with the development of entrepreneurship as well as the principal tasks aimed at enhancing the entrepreneurship in the NKR. Проблемы экономической стабилизации и возрождение экономики, развитие промышленности и других отраслей экономики НКР, повышения благосостояния и уровня жизни населения связано с началом проведения радикальных реформ в постсоветское время. Обеспечение развития экономики в условиях рынка в НКР требует решения этих и многих других экономических проблем, которые можно добиться лишь при создании необходимых условий для развития предпринимательства. В статье рассмотрены основные проблемы развития предпринимательства и основные задачи по активизации становления предпринимательства в НКР на современном этапе.
Keywords: Экономика